Case study of epidemiological investigation of Dengue Hemorrhagic Fever (DHF) in Blitar City - Aprillia, Shinta Meriza; Peristiowati, Yuli (Science Midwifery, 2025)
In 2024, there was an upward trend in Dengue Hemorrhagic Fever (DHF) cases in Blitar City, with a total of 135 reported cases. The Incidence Rate (IR) was 92.21 per 100,000 population, and the Case Fatality Rate (CFR) stood at 2.36%. This study aims to investigate DHF cases occurring in three Community Health Centers (Puskesmas) in Blitar City. Using secondary data sources, the highest transmission rate was recorded during the 13th epidemiological week (March 22, 2024) through the 14th week (March 25, 2024). Fatalities were reported in children aged 6 months and 10 years, with the highest Attack Rate found in the 5–14-year age group. In 2024, the Larvae-Free Index (Angka Bebas Jentik/ABJ) in Blitar City was recorded at 94.6%, slightly below the ideal target of >95%. Preventive and promotive efforts were carried out through effective Mosquito Nest Eradication (Eradication of Mosquito Breeding Places/PSN) using the 3M strategy: draining, covering, and recycling water storage containers, along with "Plus" actions such as sprinkling larvicide in hard-to-clean water containers, using mosquito repellent, sleeping under mosquito nets, breeding larva-eating fish, planting mosquito-repellent plants, installing window screens, and regularly inspecting water containers. Individuals experiencing recurrent fever with a body temperature ≥38°C for more than 3 days are advised to seek medical examination promptly and maintain adequate fluid intake. Fogging was conducted within a 200-meter radius around residences where DHF cases or confirmed diagnoses were found. Herd immunity efforts through immunization are considered a cost-effective alternative for controlling the spread of DHF